2017
DOI: 10.2147/copd.s126158
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and characterization of COPD exacerbations using real-time data collection

Abstract: IntroductionPatients with chronic obstructive pulmonary disease often experience exacerbations. These events are important as they are a major cause of morbidity and mortality. Recently, it has been increasingly recognized that patients may experience symptoms suggestive of an exacerbation but do not seek treatment, which are referred to as unreported or untreated exacerbations. Symptom diaries used in clinical trials have the benefit of identifying both treated and untreated exacerbation events.MethodsThe Kam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Underreporting of exacerbations by COPD patients was first documented in 1998 by the East London COPD study in which 50.5% of episodes in which subjects recorded symptoms of an exacerbation that were retrospectively identified from symptom diaries, were not reported to the investigators at the time they occurred 3. Similar results have been reported from the same group7 and other groups have found that between 44–82% of exacerbations are unreported 46,8,10,11. As identification of unreported exacerbations is retrospective, no clinical samples collected at the time of exacerbation are available so it is not known whether underreporting of exacerbations relates to differences in aetiology or inflammatory responses.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Underreporting of exacerbations by COPD patients was first documented in 1998 by the East London COPD study in which 50.5% of episodes in which subjects recorded symptoms of an exacerbation that were retrospectively identified from symptom diaries, were not reported to the investigators at the time they occurred 3. Similar results have been reported from the same group7 and other groups have found that between 44–82% of exacerbations are unreported 46,8,10,11. As identification of unreported exacerbations is retrospective, no clinical samples collected at the time of exacerbation are available so it is not known whether underreporting of exacerbations relates to differences in aetiology or inflammatory responses.…”
Section: Discussionmentioning
confidence: 64%
“…It is unclear whether unreported exacerbations are simply less severe exacerbations. In some studies symptoms are less severe compared with reported exacerbations,4,5,9,11 whereas others have found no differences in severity of symptoms or physiological parameters between reported and unreported exacerbations 3,68. However unreported exacerbations do have long-term significance as they are associated with impaired health status in COPD patients 6,12.…”
Section: Introductionmentioning
confidence: 98%
“…Chronic lower respiratory disease (the majority consisting of COPD) is the fourth leading cause of death in Canada 6. Furthermore, COPD is the most common cause of chronic disease hospitalization in Canada 7.…”
Section: Introductionmentioning
confidence: 99%
“…Exacerbations are characterized by increased dyspnea, increased sputum volume and new or increased sputum purulence. Of note, while patients with AATD more frequently seek treatment for dyspnea and sputum volume during disease exacerbations, 28 patients are less worried about any changes in sputum color. However, sputum color is a more reliable indicator of bacterial infection requiring antibiotic treatment and the associated increase in sputum elastase activity.…”
Section: Modifiers Of Quality Of Life In Patients With Aatd: Focus Onmentioning
confidence: 99%
“…However, sputum color is a more reliable indicator of bacterial infection requiring antibiotic treatment and the associated increase in sputum elastase activity. 29 Therefore, patients experiencing a change in sputum color ( Figure 2) should be advised to seek medical treatment and should be prescribed antibiotic therapy as early as possible to reduce exacerbation length, elastase activity, and protect lung tissues, 28 which can ultimately affect disease progression.…”
Section: Modifiers Of Quality Of Life In Patients With Aatd: Focus Onmentioning
confidence: 99%